2011
DOI: 10.1037/a0021937
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment outcome associated with the shift to empirically supported treatments in an outpatient clinic is maintained over a ten-year period.

Abstract: Recent years have seen an increase in emphasis on the use of psychological treatments that are supported by empirical data, as advocates have argued these treatments lead to better patient outcomes. We have previously shown that a shift to use of empirically supported treatments in a training clinic led to significant improvement in patient outcomes over four year « (Cukrowicz et al., 2005). In the current study, we examined whether average patient outcomes at termination continued to be favorable over the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…This belief pattern might explain the very low uptake of protocol-and manual-based treatment methods (e.g., Addis & Krasnow, 2000), despite evidence that structured treatments enhance therapy outcomes (Cukrowicz et al, 2011). Unaware of the reality of poor therapy outcomes, clinicians are likely to continue not to address issues that could help to improve their skills and help clients.…”
Section: Taken In Combination Withmentioning
confidence: 99%
“…This belief pattern might explain the very low uptake of protocol-and manual-based treatment methods (e.g., Addis & Krasnow, 2000), despite evidence that structured treatments enhance therapy outcomes (Cukrowicz et al, 2011). Unaware of the reality of poor therapy outcomes, clinicians are likely to continue not to address issues that could help to improve their skills and help clients.…”
Section: Taken In Combination Withmentioning
confidence: 99%
“…Use of manuals offer numerous advantages for clinical practice; they said the dissemination and replication of interventions, make the content of time-limited interventions more structured and focused than they might be otherwise, and facilitate training and supervision of intervention providers [10,11]. The recent increase in the pressure to employ treatment manuals has extended beyond controlled research trials into practice, and evidence is emerging, supporting the use of manuals in clinical practice [11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there are evidence-based approaches established for exposure treatments for Obsessive Compulsive Disorder (Abramowitz, Foa, & Frankiln, 2003), social skills training and cognitive behavioral group treatment for social anxiety disorder (Heimberg, Salzman, Holt, & Blendell, 1993; Herbert et al, 2005), cognitive behavioral therapy for panic disorder (McHugh, Smits, & Otto, 2009), prolonged exposure for PTSD (Foa, Hembree, & Rothbaum, 2007), exposure for specific phobia (Emmelkamp, Bowman, & Scholing, 1995), and more recently for the approach of mindfulness for generalized anxiety (Vollestad, Sivertsen, & Nielson, 2011). Additionally, Curkowicz et al (2011) found evidence that shifting to empirically supported treatments in a training clinic led to significant improvements in patient outcomes that was maintained for a period up to 10 years (Curkowicz et al, 2011). …”
Section: Introductionmentioning
confidence: 99%